Teachers Conception, Attitude and Practices of Educational Technology - Mir Zaman,Muhammad Athar Hussain, Abdul Ghafar, Sheraz Khan (PJDOL, 2023)
Purpose of this study was to investigate teachers' conceptions, attitude and practices of educational technology. Mixed-methods approach was adapted for this study. Sample of the study was 300 secondary school teachers. Self-designed questionnaire containing 15 items was administered for quantitative data, while interview was conducted with ten teachers.